Embryonal Tumor With Multilayered Rosettes of the Parietooccipital Region: A Case Report. Issue 1 (January 2022) - Horwitz, Jennifer; Huang, Annie; McAuley, David; Jansen, Gerard H.; Johnston, Donna
Abstract : Embryonal tumor with multilayered rosettes is a rare and highly malignant early childhood brain tumor. We report a case of embryonal tumor with multilayered rosettes in the parietooccipital region of a 2-year-old girl. Histopathology of the tumor demonstrated amplification of the 19q13.42 locus and strong positivity for LIN28A. Treatment was multimodal and included 3 surgical resections, adjuvant chemotherapy with autologous stem cell rescue, and focal radiotherapy. The use of the agents vorinostat and isotretinoin, and the addition of focal radiation have not been extensively described in this patient population, but may attribute to our patient's sustained remission at 2.5-years follow-up.